Impact of Monetary Policy on the Profitability of Nepalese Commercial Banks - Ghimire, Shiva Raj; Aryal, Narayan Prasad; Basnet, Ashok (Interdisciplinary Journal of Management and Social Sciences, 2024)
This study examines the impact of monetary policy instruments on firm profitability in Nepalese commercial banks from 2007/08 to 2021/22. The research investigates the relationship between profitability and various monetary policy instruments, including broad money supply, statutory liquidity ratio, bank rate, investment in treasury bills, and cash reserve ratio. The analysis reveals diverse return on investment (ROI) trends across banks, with NIMBL initially showing high ROI followed by a drop, SBL and SBI displaying substantial increases, and NABIL and HBL maintaining stable ROI. Net Interest Margin (NIM) analysis shows varying profitability, while monetary policy indicators exhibit diverse and occasionally fluctuating values, influencing borrowing costs and liquidity. Correlation analysis identifies positive associations between NIM, M2, and ROI and negative correlations with TBR and CRR. Regression analysis emphasizes the significance of CRR, IRS, and M2 in impacting ROI. The study concludes that the cash reserve ratio, bank rate, and investment in treasury bills affect Nepalese commercial banks’ profitability. Recommendations include managing the cash reserve ratio, maintaining low bank rates, encouraging treasury bill investment, and minimizing the statutory liquidity ratio to enhance profitability. Implications suggest that effective management of monetary policy instruments can improve banks’ profitability. Future research could explore additional profitability indicators, expand the sample size and observation years, include other financial institutions, and employ a mixed-method approach for a comprehensive understanding of the impact of monetary policy instruments on bank profitability.